QTL Analysis and Nested Association Mapping for Adult Plant Resistance to Powdery Mildew in Two Bread Wheat Populations - Ren, Yan; Hou, Weixiu; Lan, Caixia; Basnet, Bhoja R.; Singh, Ravi P.; Zhu, Wei; Cheng, Xiyong; Cui, Dangqun; Chen, Feng (Frontiers in Plant Science, 2017)
CIMMYT wheat (Triticum aestivum L.) lines Francolin#1 and Quaiu#3 displayed effective and stable adult plant resistance to Chinese Blumeria graminis f. sp. tritici isolates in the field. To elucidate their genetic basis of resistance, two recombinant inbred line (RIL) populations of their crosses with Avocet, the susceptible parent， were phenotyped in Zhengzhou and Shangqiu in the 2014–2015 and 2015–2016 cropping seasons. These populations were also genotyped with the simple sequence repeat markers and DArT-array platform. Two common significant quantitative trait loci (QTL) on wheat chromosomes 1BL and 4BL were detected in both populations by joint and individual inclusive composite interval mapping, explaining 20.3-28.7% and 9.6-15.9% of the phenotypic variance in Avocet × Francolin#1 and 4.8-11.5% and 10.8-18.9% in Avocet × Quaiu#3, respectively. Additional QTL were mapped on chromosomes 1DL and 5BL in Avocet × Francolin#1 and on 2DL and 6BS in Avocet × Quaiu#3. Among these, QPm.heau-1DL is probably a novel APR gene contributing 6.1-8.5% of total phenotypic variance. QTL on 1BL corresponds to the pleiotropic multi-pathogen resistance gene Yr29/Lr46/Pm39, whereas the QTL on 2DL maps to a similar region where stripe rust resistance gene Yr54 is located. The QTL identified can potentially be used for the improvement of powdery mildew and rust resistance in wheat breeding.